Pre-clinical development of a wireless neural interface system for osseointegrated prosthetic control in sheep - Sears, Lucas; Deshmukh, Ashlesha; Mereddy, Rishith; Go, Vinson; Nemke, Brett; Lu, Yan; Zeng, Weifeng; Suminski, Aaron J.; Markel, Mark; Bachus, Kent N.; Morizio, James; Poore, Sam O.; et al. (Frontiers in Neuroscience, 2025)
The Osseointegrated Neural Interface (ONI) is an innovative peripheral nerve interface design that houses a transected nerve and coupled electrical components within the medullary canal of long bones for eventual prosthetic control. Before the ONI can enter clinical testing, it must demonstrate longitudinal durability in an animal model analogous to the human anatomy. Adult sheep, possessing comparable weight and bone structure to adult humans, serve as the standard model for osseointegration research, solidifying them as the ideal animal for the development of an ONI. In this paper, we introduce an Ovine ONI model with a wireless, dual capsule implantable peripheral nerve interface capable of remote stimulation and recording of our subject’s nervous system 8 weeks post-implantation. This study investigates the interface design, surgical methodology, radiological evidence, and electrophysiological data that substantiate the osseointegrated approach to interfacing with the peripheral nervous system. We also explore the functional specifications, 3D printing, and coating processing steps for the capsule. Furthermore, our exploration includes the post-processing data analysis methodology used to validate our interface. This methodological study not only contributes crucial insights but also establishes the essential foundation for future goals of the ONI project. Emphasizing real-world applicability through closed-loop interfacing and enhanced efficacy of recording devices.